Basal Cell Carcinoma with Spontaneous Regression: A Case Report and Immunohistochemical Study - Taku Fujimura; Aya Kakizaki; Yumi Kambayashi; Setsuya Aiba (Karger Publishers, 2012)
Spontaneous regression of basal cell carcinoma (BCC) is rare, and characterized by various tumor-infiltrating lymphocytes (TILs) in the tumor. A previous report suggested that these infiltrated lymphocytes consist of type 1 helper T cells, but no detailed phenotypical analysis of other TILs has been demonstrated yet. In this report, we describe an 84-year-old Japanese patient with spontaneous regression of BCC. In the present case, we investigated the immunohistochemical profiles of TILs, not only focusing on the cytotoxic T cells, but the profiles of immunosuppressive cells, such as regulatory T cells and tumor-associated macrophages. Our present study sheds light on the immunological mechanisms of tumor rejection in human BCC.